2012
DOI: 10.2478/s11756-012-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A kinase interacts with and phosphorylates VHL protein

Abstract: Abstract:The serine/threonin kinase Aurora A is an oncoprotein, whereas von Hippel-Lindau protein (pVHL) is a tumor suppressor protein. Both proteins have the same localization during mitosis: in the mitotic spindle and the centrosome. These two proteins also have common functions, such as the regulation of the cell cycle, the stability of the mitotic spindle and both intervene in the functioning of centrosomes. In this study we have analyzed the interaction between Aurora A and pVHL with immunoprecipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Altogether, the expression levels of the oncoprotein Aurora A and tumor suppressor pVHL correlate in an opposite manner and one has to better investigate to which extent a high level of Aurora A expression associated to a reduction in pVHL expression could be considered as a molecular signature of a high TNM stage and of a bad prognosis. Considering, Aurora A /pVHL interaction [47,48], it could be assumed that the decrease of pVHL could lead or at least participate to Aurora A overexpression [18]. Based on such results and on the observations of the present paper, it could be proposed that absence of Aurora A protein associated to a strong expression of pVHL in clear cells kidney carcinoma are of good prognosis for the disease.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Altogether, the expression levels of the oncoprotein Aurora A and tumor suppressor pVHL correlate in an opposite manner and one has to better investigate to which extent a high level of Aurora A expression associated to a reduction in pVHL expression could be considered as a molecular signature of a high TNM stage and of a bad prognosis. Considering, Aurora A /pVHL interaction [47,48], it could be assumed that the decrease of pVHL could lead or at least participate to Aurora A overexpression [18]. Based on such results and on the observations of the present paper, it could be proposed that absence of Aurora A protein associated to a strong expression of pVHL in clear cells kidney carcinoma are of good prognosis for the disease.…”
Section: Discussionsupporting
confidence: 63%
“…These studies included three parts and started with a study in bioinformatics where the interaction 'in silico' was predicted with strong probability, and then an 'in vitro' test using a recombinant protein was done and confirmed this interaction. Finally an 'in vivo' study with endogenous proteins on cell cultures comes to consolidate this hypothesis [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the binding does not require proline hydroxylation, while CDKN1b site-specific mutation associated with cancer is shown to modulate this novel interaction. The pVHL is also a substrate of different kinases [58][59][60][61][62] and the functional meaning of these modifications is only partially understood. Roe et al [60] reported that the phosphorylation of pVHL Ser111 by Chk2 (checkpoint kinase 2) enhances pVHL-mediated transactivation of p53 on DNA damage by recruiting p300 and Tip60 to the chromatin of p53 target genes.…”
Section: Von Hippel-lindau Protein and The Regulation Of Kinases Activitymentioning
confidence: 99%